Synthesis of a novel benzophenone derived UV absorber acrylate monomer - Bıçak, Tuğrul Cem. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2015., 2015)
Since the destructive effects of sunlight have been discovered, UV protection of materials have gained more importance. The weathering resistance of organic materials can be increased by coating their surface with UV absorber polymers. Benzophenones and triazines are the most common commercially availible UV absorbers which are sold under different trademarks. In this thesis, we have synthesized a novel benzophenone derived acrylate monomer which undergoes Photo-Fries Rearrangement when exposed to sunlight. The new compound has the ability to absorb the UV portion of the electromagnetic spectrum via proton transfer. When the radiation stops, the compound returns to its original form and release the energy as heat so that the material is protected from the UV light. The monomer was polymerized to give homopolymers and methyl methacrylate copolymers at different ratios, then the UV absorption behavior of the polymers before and after the UV radiation were investigated.
Keywords: Ultraviolet radiation.